El impacto urbano del mall aventura plaza en la urbanización la esmeralda, Trujillo - Perú - Angulo Cárdenas, Carlos Jonathan (2016)
This work master's thesis aimed to study the impact Urban Mall Aventura Plaza in the La Esmeralda, located in the district of Trujillo, in order to know if there are negative urban impacts that alter the quality of life in the said Construction and if they are significant enough to take them into account in developing mitigation policies in the city. At work positive results were found , such as diversification and increased land values for area residents and negative results as the emergence of street invading public streets , abandonment of purchases from neighboring markets to the area and increasing traffic and traffic accidents ; Using the scientific method descriptive analytical , quantitative techniques , so it is recommended governance policies , marketing surveys , road access routes and put all these instruments Urban Development Plan to prevent future negative impacts.